(untitled) (Revista Aspas, 2022)
This paper maps the experience of the Somatic-Performative Clinic developed at Universidade Federal do Estado do Rio de Janeiro since 2018, presenting the Arts research conducted therein as a type of poetics of care in the classroom. Such experience allow us to reflect on the importance of affect, joy, and collectivity for a collective artistic production.